Effects of almond consumption compared with the consumption of traditional isocaloric cereal/pulse-based snacks on glycaemic control and gut health in adults with pre-diabetes in rural India: protocol for a 16-week, parallel-arm, cluster randomised controlled trial - N Sreekumaran Nair; Vaidya Ruchi; Chaudhury Nayanjeet; Pramila Kalra; Bellur Prabhakar (BMJ Open)
Introduction Almonds have prebiotic potential to maintain gut health and regulate glycaemia. Western studies have shown their positive effects on preventing non-communicable diseases like diabetes and cardiovascular diseases. However, there is a lack of research involving Asian Indians, who have a higher predisposition to diabetes due to their unique ‘Asian phenotype’. Therefore, this study aims to evaluate the impact of almond supplementation on glycaemic control and gut health in adults with pre-diabetes in rural India through a randomised clinical trial.Methods and analysis A parallel cluster randomised controlled trial with 178 participants with pre-diabetes (assigned 1:1) aged 20–50 years, of both genders, with a body mass index of 18.9–25 kg/m2, will be conducted in rural areas of Chikkaballapur, Kolar and Rural Bangalore districts in India. The intervention group will receive 56 g of almonds as mid-morning snacks for 16 weeks, while the control group will receive cereal/pulse-based traditional isocaloric snacks under the closed supervision of the study investigators. The primary outcome of the study is HbA1c measured at the 16th week. The secondary outcomes—anthropometry, clinical and other biochemical parameters—will be measured at 0th, 8th and 16th weeks, and a subgroup of 120 participants will undergo gut health analysis. Glucagon-like peptide 1 analysis will be conducted on 30 participants at 0th and 16th weeks. Statistical analysis will be performed using SPSS for Windows V.27.0, and both intention-to-treat and per-protocol analyses will be conducted.Ethics and dissemination Ethics approval was obtained from the Institutional Ethics Committee at Ramaiah Medical College, Bangalore, Karnataka, India (DRPEFP7672021). We will obtain the informed written consent of the participants prior to screening and enrolling them in the study. Results from this trial will be disseminated through publication in peer-reviewed journals and scientific gatherings.Trial registration number Clinical Trial Registry of India (CTRI/2023/03/050421).